Survey on iodine nutrition and thyroid function in adults in Xinjiang - ABUDUWAILI Gulinaize’er; Li SUN; Jia HUANG; Yan MA (环境与职业医学, 2023)
BackgroundPrevious iodine nutrition monitoring has mainly focused on key populations such as pregnant women and children, and there are few reports on the status of iodine nutrition among adults in Xinjiang. ObjectiveTo understand the iodine nutrition and thyroid function status of healthy adults in northern and southern Xinjiang, and to explore the effect of iodine nutrition level on thyroid function. MethodsIn May 2021, a stratified cluster sampling method was used to select one county (city) with good and one county (city) with poor economic conditions in each of the northern and southern regions of Xinjiang as the survey sites, and about 100 households were sampled from each survey site to collect samples of edible salt as well as random urine samples and fastingvenous blood of healthy adults aged 18 years or older. Urinary iodine was determined by cerium arsenide catalytic spectrophotometric method, salt iodine by direct titration method, and thyroid hormones by chemiluminescence immunoassay. Non-parametric test was used for comparison of non-normal quantitative data, t-test and analysis of variance were used for comparison of normal quantitative data, χ2 test was used for comparison of rates, and Spearman correlation analysis was used for correlation between salt iodine intake and urinary iodine level. ResultsA total of 436 salt samples were collected, the median salt iodine level was 28.18 mg·kg−1, and the coverage rate of qualified iodized salt was >90% in both northern and southern Xinjiang regions (P>0.05). A total of 436 adult urine samples were collected, the median urinary iodine was 219.73 μg·L−1. The urinary iodine medians of adults in the northern and southern regions were 209.47 μg·L−1 and 244.80 μg·L−1, respectively, and it was higher in the southern region than that in the northern region (P<0.05). The mean value and abnormality rate of serum free triiodothyronine (FT3) of adults in northern Xinjiang was lower than those in southern Xinjiang (P<0.05). The positive rates of anti-thyroglobulin antibody (TgAb) were 21.39% and 9.79%, the positive rates of anti-thyroid peroxidase antibody (TPOAb) were 27.36% and 10.64%, and the positive rates of both antibodies were 16.42% and 5.53% in the northern and southern regions, respectively. The positive rates of TgAb, TPOAb, and both antibodies in northern Xinjiang were higher than those in southern Xinjiang (P<0.05). The rates of abnormal thyroid function in northern Xinjiang and southern Xinjiang were 14.43% and 13.19%, respectively, with no statistically significant differences between the regions (P>0.05), in which subclinical hypothyroidism was predominant, with prevalence rates of 9.95% and 9.36% in the northern and southern regions, respectively. ConclusionSome adults in northern and southern Xinjiang have high iodine nutrition levels, and although no significant effect has been found on thyroid function in the population, the high iodine nutrition status still requires continuing concern. It is recommended to monitor the iodine nutritional status of adults continuously while strengthening health education for residents.